2023
DOI: 10.1111/aogs.14662
|View full text |Cite
|
Sign up to set email alerts
|

One‐year follow up of contraceptive use and pregnancy rates after early medical abortion: Secondary outcomes from a randomized controlled trial of immediate post‐abortion placement of intrauterine devices

Sara Hogmark,
Niklas Envall,
Kristina Gemzell‐Danielsson
et al.

Abstract: IntroductionIntrauterine devices (IUDs) effectively prevent unwanted pregnancies. Little is known about long‐term outcomes of women choosing an IUD after early medical abortion.Material and methodsWe present secondary outcome data of continuation rates, factors associated with continuation and discontinuation, choice of IUD type, women's satisfaction with IUD, and IUD expulsions, subsequent pregnancies, and abortions within 1 year post‐abortion in a randomized, controlled, multicenter trial on IUD placement wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Long‐acting reversible contraception (LARCs), consisting of subdermal implants and intrauterine devices, are highly effective, not dependent on the user and have high continuation and satisfaction rates. 5 , 6 LARCs are increasingly recommended as first‐line choice to all women including nulliparous women and adolescents. Several studies have shown that LARCs are more effective in preventing unintended pregnancy and abortion compared to other reversible methods.…”
Section: Introductionmentioning
confidence: 99%
“…Long‐acting reversible contraception (LARCs), consisting of subdermal implants and intrauterine devices, are highly effective, not dependent on the user and have high continuation and satisfaction rates. 5 , 6 LARCs are increasingly recommended as first‐line choice to all women including nulliparous women and adolescents. Several studies have shown that LARCs are more effective in preventing unintended pregnancy and abortion compared to other reversible methods.…”
Section: Introductionmentioning
confidence: 99%